Analisis Dampak Kesepakatan Asean Dalam Pengembangan Sektor Maritim Kepulauan: Kajian Dari Perspektif KTT AIS Forum - Andini Pramudita; Lerian Kurnisa; Jessica Jessica (Polsight, 2025)
This journal conducts an in-depth analysis of the impact of ASEAN agreements on the development of the archipelagic maritime sector, with a focus on the perspective of the Archipelagic and Island States (AIS) Forum High-Level Conference. As a concrete collaboration platform, the AIS Forum becomes the subject of research to understand the contribution of ASEAN agreements in addressing the challenges faced by archipelagic nations in maritime development. This research employs descriptive and qualitative analysis methods by exploring journals, official statements, official news, and outcomes of the AIS Forum High-Level Conference. The results of the analysis indicate that ASEAN agreements through the AIS Forum High-Level Conference have a significant positive impact on strengthening Indonesia's leadership in global maritime issues. Interarchipelagic cooperation, particularly through the exchange of knowledge, technology, and resources, has proven to be a crucial factor in addressing common challenges in the maritime sector. Furthermore, the journal illustrates that the AIS Forum High-Level Conference serves as a platform for the aspirations and hopes of archipelagic communities, with the interests of the people being the primary focus in maritime sector development. Concrete programs, such as mangrove restoration and addressing the impacts of climate change, implemented through the AIS Forum, not only support the blue economy but also enhance environmental awareness among communities. The empowerment of local communities through sustainable governance and the management of maritime resources becomes a key element in creating sustainable positive impacts at the local level.